Addressing the global burden of hepatitis B virus while developing long-acting injectables for the prevention and treatment of HIV. Issue 6 (June 2020) - Bollinger, Robert C; Thio, Chloe L; Sulkowski, Mark S; McKenzie-White, Jane; Thomas, David L; Flexner, Charles
Summary: The first long-acting formulations of HIV drugs are undergoing regulatory review for use in maintenance of viral suppression in people with HIV. Although these novel drug formulations could contribute greatly to HIV treatment and prevention efforts, their lack of activity against hepatitis B virus (HBV) could limit their global impact, particularly in populations with high burdens of both HIV and HBV. An urgent need for greater investment in research and development of long-acting drugs with dual activity against HIV and HBV exists. Access to long-acting HIV drug formulations with dual activity against HBV would be transformative and have a great impact on efforts to prevent, treat, and eradicate both of these important global epidemics.